Modeling growth, yield, irrigation water use and soil moisture dynamics of OPSIS-irrigated sugarcane - M. H. J. P. Gunarathna; M. K. N. Kumari (Frontiers in Sustainable Food Systems)
The Optimized Subsurface Irrigation System (OPSIS) is a neoteric subsurface irrigation method designed for irrigating upland crops. While field trials have evaluated its performance for certain crops, further research is required to enhance its effectiveness. Utilizing crop models to assess OPSIS could reduce the need for time-consuming and costly field trials. This study aimed to enhance the modeling capabilities of the Agricultural Production Systems Simulator (APSIM) to simulate the growth, yield, water use, and soil moisture dynamics of OPSIS-irrigated sugarcane (Saccharum officinarum L.). Field trial data from Okinawa, Japan, spanning three growing seasons (including the main crop and two ratoons), two distinct planting seasons (spring and summer planting), and two different crops were collected to calibrate and validate the newly developed module linking OPSIS with the APSIM engine. We parameterized, calibrated, and validated the APSIM-Sugar model to simulate the growth, yield, water use, and soil moisture dynamics of OPSIS irrigated sugarcane. APSIM-Sugar successfully represented the growth and yield of OPSIS-irrigated sugarcane. However, the simulation of soil moisture dynamics and irrigation water usage fell short of expected standards. Further research is recommended to improve the simulation accuracy of soil water dynamics and irrigation water usage for OPSIS-irrigated sugarcane.